2022-RA-1258-ESGO Patient walk to the operating theatre as a new tool for patient empowerment – KORE-INNOVATION: the first prospective clinical trial to assess a perioperative pathway to reduce postoperative complications in ovarian cancer patients. (20th October 2022) - Lee, Marlene; Inci-Turan, Melisa Guelhan; Hellmich, Sarah; Heinemann, Ruth; Schneider, Stephanie; Schnura, Eva; Klews, Julia; Niggemann, Phil; Sehouli, Adak Pirmorady; Gizycki, Thyra von; Zwanzleitner, Lena; Algharably, Engi; et al.
Abstract : Introduction/Background: Patient empowerment is an essential, yet neglected resource of the patient's health journey. Through a patient-centered approach, patients are encouraged to take on an active role in their health and recovery. We report our first experiences of the patient walk intervention as part of the patient empowerment module, which is embedded in the KORE-INNOVATION trial as a subpopulation analysis. Methodology: The KORE-INNOVATION trial is an ongoing clinical trial to assess an innovative perioperative care pathway to reduce complications for patients undergoing surgery for ovarian cancer. We implemented the patient walk intervention to encourage patients' autonomy before surgery. Patients were given the option to walk to the operation room instead of being pushed in their bed as part of the standard patient care pathway. The only requirement for walking was to omit sedating pre-medication. To evaluate patients' and staff's experiences, we administered a questionnaire between the 2nd-5th postoperative day. Results: Of the 65 patients offered to walk to the operating room, 48 participated. All patients reported that the experience was either better than expected or as expected; nobody reported that it was worse than expected. Patients reported that if given the choice would walk again. Patients also stated that they felt strengthened in their autonomy. Reasons for not walking were refusal to omit sedatives or anxiety before the operation. The main barriers from the staff's perspective were logistical difficulties, which decreased over time. Conclusion: Providing patients with the option to walk to the operating theatre is a simple but effective method of increasing patients' autonomy and engagement. Furthermore, it promotes the active patient role in their health and recovery. This easily implementable no-cost intervention should be routinely integrated in the context of ERAS protocols.